A student grammar of modern standard Arabic - Schulz, Eckehard (Cambridge University Press, 2004)
This accessible grammar provides a concise and user-friendly guide to the structure of Modern Standard Arabic. Using familiar terminology and keeping theory to a minimum, it is suitable for beginning students as well as those at a more advanced level. Detailed descriptions of all types of sentence are given, and numerous tables provide a clear presentation of verbs and nouns. The most familiar grammatical terms are given in Arabic as well as in English in order to help the student identify them, and the index is also presented in both languages for fast and straightforward cross referencing. Each pattern or rule described is illustrated with authentic examples from a range of real-life contexts such as newspapers, magazines, business communication and the Internet, as well as from Arabic literary texts. Clearly organised and practical, this book will be an invaluable reference resource for all learners and teachers of Modern Standard Arabic